Prevalence of vitamin D deficiency in patients with established coronary artery disease - Kaur, Sapneet; Kaur, Harleen; Sharma, Susheel Kumar; Bhatia, Amarjeet Singh (International Journal of Research in Medical Sciences, 2020)
Background:Vitamin D deficiency is widely prevalent in this part of the country, in spite of the fact that there is ample sunshine and the economic status of the people is good. Several studies have suggested possible link between vitamin D deficiency and cardiovascular disease risk. Hence authors evaluated the patients with established coronary artery disease attending cardiology department of super speciality hospital, Government Medical College Jammu, for their vitamin D status. Methods:The study was conducted in the department of Biochemistry Government Medical College Jammu and data of established cases of coronary artery disease patients attending cardiology department of super speciality hospital, government medical college Jammu was analyzed for vitamin D levels during the period from January 2019 to February, 2020. Results: A total of 200 established cases of coronary artery disease comprising of 130 male patients and 70 female patients were analyzed in the study, out of 200 cases, 190 (95%) were found to be having low levels of vitamin D in their blood (<30 ngm/dl). 123 (94.6%) out of a total of 130 male patients had vitamin D deficiency as compared to 67 (95.7%) out of 70 females patients. Conclusions:The study has revealed a very high prevalence of vitamin D deficiency in established cases of coronary artery diseases. More detailed prospective studies are required to unravel the association of vitamin D and its role in prevention of coronary artery diseases in the absence of well-established risk factors like smoking, Diabetes, Hypertension and dyslipidaemias.